Interleukin-13 gene polymorphisms and asthma susceptibility in children: a meta-analysis - Song Su; Tong Zhang; Yaping Wang; Huan Zhang; Meng Wang; Wandong Hu; Ying Ren; Fen Zhao; Hongwei Zhang (BMC Pediatrics)
Abstract Background Interleukin (IL)-13 is a central mediator of airway inflammation in asthma, and gene polymorphisms may play a role in asthma pathogensis. However, the relationship between IL-13 gene polymorphisms and asthma susceptibility remain unclear. Therefore, we conducted this meta-analysis to evaluate this relationship and better understand the risk of asthma in Chinese children. Methods and Results PubMed, cnki.net, China Wanfang, and Embase were searched to identify relevant case–control studies in Chinese children published until July 2021. In total, 217 Chinese and English articles were searched; 23 articles were included (19 Chinese and 4 English). Compared with genotype CC and allele C, genotypes TT, TC, and TT + TC at the rs1800925 (C-1112 T) loci and allele T, respectively, were not associated with the risk of bronchial asthma. At the rs1295686 (C + 1923 T) loci, compared with genotype CC, there were significant associations between genotypes TT, TC, and TT + TC and the risk of bronchial asthma. Compared with allele C, allele T increased the risk of bronchial asthma. At the rs20541 (G + 2044A) loci, compared with genotype GG, the genotypes AA and AA + GA were associated with the risk of bronchial asthma, but the genotype GA was not. Compared with allele G, allele A increased the risk of bronchial asthma. Conclusions rs1295686 (C + 1923 T) and rs20541 (G + 2044A) gene polymorphisms are associated with asthma susceptibility, whereas rs1800925 (C-1112 T) gene polymorphisms are not.